2019
DOI: 10.1016/j.nicl.2019.101891
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar atrophy and its contribution to motor and cognitive performance in multiple system atrophy

Abstract: Objective Neuroanatomical differences in the cerebellum are among the most consistent findings in multiple system atrophy (MSA) patients. This study performed a detailed cerebellar morphology in MSA patients and its two subtypes: MSA-P (parkinson's symptoms predominate) and MSA-C (cerebellar symptoms predominant), and their relations to profiles of motor and cognitive deficits. Materials and methods Structure MRI data were acquired from 63 healthy controls and 61 MSA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
7
20
0
Order By: Relevance
“…Atrophy of the cerebellum and brainstem are common features of MSA‐C and SAOA . In addition, microstructural alterations of the white matter have been reported in previous studies in MSA‐C patients .…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Atrophy of the cerebellum and brainstem are common features of MSA‐C and SAOA . In addition, microstructural alterations of the white matter have been reported in previous studies in MSA‐C patients .…”
mentioning
confidence: 62%
“…Previous volumetric and VBM studies in MSA‐C have consistently shown cerebellar and brainstem volume loss . In SAOA, volume loss has been reported as being most prominent in the cerebellum, although some studies also detected involvement of the cerebellar peduncles and brainstem.…”
Section: Discussionmentioning
confidence: 92%
“…The synergistic effect of the cerebellum with the frontal network has indicated that aside from its traditional integration of motor function, the cerebellum also participates in the regulation of non-motor functions such as cognition. Yang et al (2019) reported that cerebellar abnormalities in patients with MSA are related to the cognitive impairment process. Wang et al (2018) suggested that the cerebellum plays a key role in emotion regulation in PD patients with depression.…”
Section: Discussionmentioning
confidence: 99%
“…• Structural MRI MRI signs: putaminal rim sign, hot cross bun sign, middle cerebellar peduncles (MCP) sign Striatonigral and olivopontocerebellar atrophy is observed in MSA vs. NC ↓ in putamen, MCP, cerebellum, and pons in MSA-P vs. PD Supratentorial atrophy (putamen) in MSA-P, whereas infratentorial atrophy in MSA-C may be more predominant (11,28,71,99,102,103,(106)(107)(108)(109)(110) (Continued) • Proton MRS ↓ NAA/Cr ratio in putamen in MSA-P, and in pontine base in both MSA-P and MSA-C vs. NC ↓ NAA/Cr ratio in putamen and pontine base may discriminate MSA-P from PD (120) • PET and SPECT b Glucose metabolism: MSA-related spatial covariance pattern may involve metabolic ↓ in putamen and cerebellum (273,279) Dopaminergic system: b ↓ striatal presynaptic DAT binding and ↓ dopamine D2 receptor binding vs. NC (225,241,242) Neuroinflammation: ↑ microglial activity in dorsolateral prefrontal cortex, putamen, pallidum, pons, and SN vs. NC (332) • Transcranial S b ↑ LN echogenicity along with normal or ↑ SN echogenicity may be seen (188,197) AD clinical outcomes (320). Some of the developmental challenges [see reference (321)], although similar to those of tau PET radiotracers, include the intracellular nature of most α-synuclein aggregates requiring ideal lipophilicity and molecular size, multiple α-synuclein strains that may interact differently with some tracers, colocalization of α-synuclein with other protein aggregates, relatively less abundance of α-synuclein over amyloid and tau aggregates requiring higher tracer selectivity, as well as the potential for off-target binding which may necessitate further validation.…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Likewise, VBM analysis in MSA-P vs. PD revealed atrophy in the superior cerebellar peduncle (SCP), MCP, cerebellum, pons, midbrain, and putamen, but not in the globus pallidus ( 71 ). Cerebellar atrophy was evident in both MSA-P and MSA-C subtypes to varying degrees ( 28 , 108 ). In an analysis of cerebellar neuroanatomical differences in MSA subtypes, a relatively greater GM atrophy was observed in MSA-C cases (vs. MSA-P) in the right Crus II—a cerebellar region involved in executive motor control ( 108 ).…”
Section: Structural Neuroimaging In Parkinsonian Disordersmentioning
confidence: 99%